Phytochorme regulation of plant immunity in vegetation canopies - Moreno, Javier Edgardo (2014)
Plant immunity against pathogens and herbivores is a central determinant of plant fitness in nature and crop yield in agroecosystems. Plant immune responses are orchestrated by two key hormones: jasmonic acid (JA) and salicylic acid (SA). Recent work has demonstrated that for plants of shade-intolerant species, which include the majority of those grown as grain crops, light is a major modulator of defense responses. Light signals that indicate proximity of competitors, such as a low red to far-red (R:FR) ratio, down-regulate the expression of JA- and SA-induced immune responses against pests and pathogens. This down-regulation of defense under low R:FR ratios, which is caused by the photoconversion of the photoreceptor phytochrome B (phyB) to an inactive state, is likely to help the plant to efficiently redirect resources to rapid growth when the competition threat posed by neighboring plants is high. This review is focused on the molecular mechanisms that link phyB with defense signaling. In particular, we discuss novel signaling players that are likely to play a role in the repression of defense responses under low R:FR ratios. A better understanding of the molecular connections between photoreceptors and the hormonal regulation of plant immunity will provide a functional framework to understand the mechanisms used by plants to deal with fundamental resource allocation trade-offs under dynamic conditions of biotic stress.